Space-Based ADS-B Latency Evaluation in Jakarta and Makassar Flight Information Regions - Anastasia Andini Yuanita; Dian Anggraini; Didik Sulistyo (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
This study evaluates the latency performance of Space-Based Automatic Dependent Surveillance–Broadcast (ADS-B) within the Jakarta and Makassar Flight Information Regions (FIRs). A quantitative comparative analysis is conducted using secondary data obtained from Aireon’s operational trials in Indonesia, processed through statistical filtering to assess end-to-end latency distributions. The results show a stable average latency ranging from 0.46 to 0.48 seconds, with 95th percentile values consistently remaining below 0.5 seconds, satisfying international aviation surveillance performance requirements. These findings confirm that Space-Based ADS-B is capable of supporting reliable real-time surveillance operations in Indonesian airspace. This study contributes a QoS-based latency assessment that highlights the need for harmonized, satellite-oriented surveillance performance standards beyond existing ground-based ADS-B regulations.